(untitled) (Lakar: Jurnal Arsitektur, 2026)
This study examines how urban memory is negotiated within the contemporary metropolitan expansion of Depok City through a case study of Depok Lama. Using a qualitative case-study approach, the research integrates historical map analysis, urban morphological assessment, and field observation to trace spatial, functional, and symbolic transformations from the late colonial period to the present. The findings reveal that urban development has prioritised economic intensification and land-use optimisation, resulting in the gradual fragmentation of colonial spatial structures and the weakening of their social coherence. Although several colonial artefacts remain physically intact, their integration within the contemporary urban system is increasingly discontinuous, producing a disjunction between form, function, and meaning. Depok Lama thus illustrates a condition that may be termed survival without continuity, where material persistence does not ensure symbolic endurance. The crisis of urban memory in this metropolitan periphery is driven not by physical erasure alone, but by the erosion of relational continuity between spatial structure, social practice, and collective meaning. This study positions urban memory as an active framework for understanding and guiding transformation in historic urban areas undergoing rapid metropolitan change.